If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -24 = x + 9 Reorder the terms: -24 = 9 + x Solving -24 = 9 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -24 + -1x = 9 + x + -1x Combine like terms: x + -1x = 0 -24 + -1x = 9 + 0 -24 + -1x = 9 Add '24' to each side of the equation. -24 + 24 + -1x = 9 + 24 Combine like terms: -24 + 24 = 0 0 + -1x = 9 + 24 -1x = 9 + 24 Combine like terms: 9 + 24 = 33 -1x = 33 Divide each side by '-1'. x = -33 Simplifying x = -33
| 4x-2-2x-3=10x | | 4x+1=-23 | | 4u+46=-2(u+4) | | .25y-2x=5 | | .20x+y=3 | | 4x+5x=12 | | x-50.00=.80(x-100.00) | | 2d+.167=6(0.3d+1) | | 3(u-1)=9u-39 | | x^2=16*x | | .80(x-100.00)=450 | | -27.23+x=9.77 | | 38x-x^2=0 | | 8x+47=-9(x-9) | | 8(u-8)=3u-34 | | -139=-x+117 | | 40=3X+16 | | -35=-2w+5(w-4) | | 14y^2-37y=0 | | 20=-8y+6(y+4) | | x^2-y^2=2 | | 20=8y+6(y+4) | | k=22-2k+14 | | k=22-2k | | 3h=h+6 | | 6p+32-4p=22 | | 2d+c+4=0 | | 15x+3=3(5x+1) | | 5(3x+1)=15x | | 5x-6=12(0.75x-0.3)+10 | | 5x-14=16+10x | | x^2-6x+3y+6=0 |